Molecular diagnosis and direct quantification of cereal cyst nematode (Heterodera filipjevi) from field soil using TaqMan real-time PCR - Jin-zhuo JIAN; Wen-kun HUANG; Ling-an KONG; Heng JIAN; Sulaiman ABDULSALAM; De-liang PENG; Huan PENG (Journal of Integrative Agriculture, 2023)
Heterodera filipjevi continues to be a major threat to wheat production worldwide. Rapid detection and quantification of cyst nematodes are essential for more effective control against this nematode disease. In the present study, a TaqMan-minor groove binder (TaqMan-MGB) probe-based fluorescence quantitative real-time PCR (qPCR) was successfully developed and used for quantifying H. filipjevi from DNA extracts of soil. The primers and probe designed from the obtained RAPD-SCAR marker fragments of H. filipjevi showed high specificity to H. filipjevi using DNA from isolates-confirmed species of 23 Heterodera spp., 1 Globodera spp. and 3 Pratylenchus spp. The qPCR assay is highly sensitive and provides improved H. filipjevi detection sensitivity of as low as 4–3 single second-stage juvenile (J2) DNAs, 10–3 female DNAs, and 0.01 μg μL–1 genomic DNAs. A standard curve relating to the threshold cycle and log values of nematode numbers was generated and validated from artificially infested soils and was used to quantify H. filipjevi in naturally infested field soils. There was a high correlation between the H. filipjevi numbers estimated from 32 naturally infested field soils by both conventional methods and the numbers quantified using the qPCR assay. qPCR potentially provides a useful platform for the efficient detection and quantification of H. filipjevi directly from field soils and to quantify this species directly from DNA extracts of field soils.